Christmas around the world - Kelley, Emily; Kiedrowski, Priscilla (Minneapolis, Minnesota Carolrhoda Books, 1986)
Describes Christmas traditions in Mexico, Iran, China, Sweden, Iraq, Spain, and Norway.
56598